Residual decontamination chemical agents negatively affect adhesion and proliferation of osteoblast-like cells on implant surface - Balderrama, Isis de Fatima [UNESP]; Cardoso, Matheus Volz; Stuani, Vitor Toledo; Oliveira, Rodrigo Cardoso; Matos, Adriana Arruda; Aguiar Greghi, Sebastiao Luiz; Passanezi Sant'Ana, Adriana Campos (Springer, 2020)
Purpose To investigate the influence of implant surface decontaminated and uncontaminated on osteoblast-like cell adhesion and proliferation Materials and methods Commercially available implants of different brands and surface characteristics were selected: Biomet 3i (R) Nanotite (NT) and Osseotite (OT), Straumann (R) SLActive (SLA), and Neodent (R) Acqua Drive (ACQ) and Neoporos Drive CM (CM). Physical and chemical properties of the implants were investigated by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and wettability analysis (WETT). Implants were previously contaminated with Aggregatibacter actinomycetemcomitans strains; after that, samples were decontaminated by different chemical methods. Decontaminated (test group; n = 15/type of implant) and uncontaminated (control group; n = 5/type of implant) samples were analyzed according to the number of human osteoblastic osteosarcoma cells (Saos-2) adhered on the implant surface after 24 h and 72 h in SEM images. Results ACQ was found to be highly hydrophilic, and NT was the most hydrophobic implant. Increased variation of Saos-2 cell adhesion and proliferation were observed on all test and control groups. Controversially, at the proliferation analysis in 72 h, CM implant was the only implant that showed no significant difference between test and group (p = 0.2833; Tukey's multiple comparisons test). NT implants showed the greater value of cell proliferation when compared with all types of implant surface (p = 0.0002; Tukey's multiple comparisons test). Conclusions These findings suggest that decontaminated surfaces were able to impair the counting of osteoblast-like cell adhesion and proliferation.
Keywords: Dental implants; Decontamination; Osteoblast-like cells; Implant surface; Peri-implantitis